The secret book of Flora Lea : a novel [large type] - Henry, Patti Callahan (Center Point Large Print, 2023)
"In the war-torn London of 1939, fourteen-year-old Hazel and five-year-old Flora are evacuated to a rural village to escape the horrors of the Second World War. Living with the kind Bridie Aberdeen and her teenage son, Harry, in a charming stone cottage along the River Thames, Hazel fills their days with walks and games to distract her young sister, including one that she creates for her sister and her sister alone -- a fairy tale about a magical land, a secret place they can escape to that is all their own. But the unthinkable happens when young Flora suddenly vanishes while playing near the banks of the river. Shattered, Hazel blames herself for her sister's disappearance, and she carries that guilt into adulthood as a private burden she feels she deserves. Twenty years later, Hazel is in London, ready to move on from her job at a cozy rare bookstore to a career at Sotheby's. With a charming boyfriend and her elegantly timeworn Bloomsbury flat, Hazel's future seems determined. But her tidy life is turned upside down when she unwraps a package containing an illustrated book called Whisperwood and the River of Stars. Hazel never told a soul about the imaginary world she created just for Flora. Could this book hold the secrets to Flora's disappearance? Could it be a sign that her beloved sister is still alive after all these years?"--